Impact of Lockdown due to COVID-19 Pandemic on Undergraduate Ophthalmology Teaching: Students’ and Teachers’ Perspective - Adnan Matheen (JCDR Research and Publications Private Limited, 2021)
Introduction: Coronavirus Disease-2019 (COVID-19) pandemic has forced the union government to close the educational institutions. The medical teaching had to go digital. Digital learning has advantages but not without limitations and challenges. Aim: To analyse the impact of lockdown due to COVID-19 pandemic on undergraduate ophthalmology teaching and learning and explore the perception of faculty and students regarding its advantages, limitations and recommendations. Materials and Methods: This cross-sectional survey was conducted among ophthalmology faculty and pre final year students from six government and 11 private medical colleges through online Google questionnaire which was initially validated by three faculty and 10 students had Cronbach’s value-0.70. Based on the pilot study, the questionnaire was modified. Valid responses were entered in data sheets and Statistical Package for the Social Sciences (SPSS) version 24.0 was used to analyse the data. Chi-square test was used to find out the association between symptoms post online classes and duration of online classes and gender of the students. The p-values <0.05 were considered significant. Results: Approximately, 1500 students and 65 faculty were approached online. Out of which there were 1015 respondents, 967 valid responses were considered for analysis (929 students and 38 faculty). More than 70% of the students used mobile phone for attending online classes. Zoom (≈40%) and Google meet (≈30%) were the commonly used applications. A total of 79.3% of medical students and 84.2% of faculty disagreed to continue with online classes after the pandemic. Lack of faceto-face interaction, practical demonstration and on-campus life, connectivity issues and eye symptoms post online classes were the major disadvantages. Availability of gadgets, internet connectivity and self-discipline were the major challenges faced. The ocular symptoms were marginally more in females (p-value >0.05) and in those with extended duration of attending online classes (p-value <0.05). Post online lectures, none of the faculty had non-ocular symptoms. In comparison to the medical students, 78.9% of the faculty (30/38) always maintained proper screen position whereas 64.4% of students (598/929) did not always maintain proper screen position. Conclusion: According to this study, learners preferred less duration of online classes, improvement in e-teaching quality with interactive lectures and demonstration. Teachers preferred improved infrastructure and network connectivity. This study gives an insight of students and teachers mentality towards the online ophthalmology classes.